Prevention of parasites of fresh water shrimp (Atya gabonensis) from Rivers in Makurdi - Olagunsoye F. Rotimi; Fatou B. Dabir; Toyin F.O (Advances in Aquaculture and Fisheries Management, 2014)
The study investigated the parasitic prevalence of freshwater shrimps (Atya gabonensis) in the lower Benue River for a period of six months (March – August, 2012) during which a total of 1000 shrimps were sampled randomly from the landing sites of the River Benue and were analyzed at the parasitology laboratory of the verterinary teaching hospital, University of Agriculture, Makurdi. The gills of shrimps had the highest parasitic prevalence of 50.36% and the intestine with the lowest parasitic prevalence of 5.40%. Shrimps were infected more with ciliates with prevalence rate of 49.37% and less infected with cestodes with prevalence rate of 6.43%. Monthly condition factor shows that in March, April, June and July there was a significant difference(P< 0.05) between male and female, but there was no significant difference (P>0.05) between male and female in May and August. Correlation between weight and infection, total length and infection, weight and total length of A. gabonensis shows that correlation between weight and infection r=0.008, total length and infection r=0.007 and correlation between weight and total length r=0.853 and has a significant difference. It was observed that the number of shrimps infected with parasite was associated with sex.